2004
DOI: 10.1139/y04-024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen replacement treatment on ischemic preconditioning in isolated rat hearts

Abstract: In the present study, we tested the effects of long-term estrogen replacement treatment on myocardial ischemia-reperfusion injury and on the cardioprotection of ischemic preconditioning in isolated hearts from ovariectomized rats. Ovariectomized rats were treated with 17beta-estradiol (30 micro g/kg/d, s.c.) for 12 weeks. Isolated rat hearts were perfused in the Langendorff mode. Heart rate, coronary flow, left ventricular pressure and its first derivative (+/-LVdp/dtmax) were recorded. Fifteen-min global isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In our study, the microcirculatory manifestations of reduced efficacy of IPC after OVX were demonstrated for the first time, but similar reactions were observed with other manifestations of postischemic tissue injury in other organs by others (i.e., cardiac dysfunction) . The consequences of E2 supplementation in these scenarios, however, are not at all clear.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In our study, the microcirculatory manifestations of reduced efficacy of IPC after OVX were demonstrated for the first time, but similar reactions were observed with other manifestations of postischemic tissue injury in other organs by others (i.e., cardiac dysfunction) . The consequences of E2 supplementation in these scenarios, however, are not at all clear.…”
Section: Discussionsupporting
confidence: 78%
“…The results are somewhat controversial, as the protective effects of IPC were present in OVX rabbits . Also, E2 did not exert any alleviating effects in other studies where IPC was combined with OVX . Furthermore, long‐ and short‐term estrogen administration produced different effects, and inter‐species and inter‐organ differences and dissimilarities cannot be ruled out either .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Surgical ovariectomy has been shown to exacerbate myocardial oxidative stress-induced damage caused by anthracycline administration (50), and estrogen administration protects against ischemia-reperfusion injury (6,57). This suggests that the cardiac dysfunction observed in hearts from chemically ovariectomized rats in the present study may be attributed to compromised antioxidant status.…”
Section: Discussionmentioning
confidence: 58%
“… 8 12 Likewise, the data regarding whether chronic oestrogen depletion interferes with the development of IPC have not been entirely consistent. 20 22 The apparent discrepancy in the previous reports might be due, at least in part, to different experimental models ( in vivo vs. ex vivo ), different I/R or IPC protocols, different parameters used to assess myocardial damage, and, possibly, species differences. Song et al .…”
Section: Discussionmentioning
confidence: 97%